Indonesia’s Experience: Implementing Gender Responsive Planning and Budgeting - Fithriyah (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2017)
This paper is a historical review of Indonesia’s experience in implementing Gender Responsive Planning and Budgeting (GRPB). National Development Planning Agency/ Bappenas has initiated the implementation of gender mainstreaming in Indonesia’s national development planning policies since 1999. It was started in 1998 by developing the Gender Analysis Pathway, the tool for conducting gender analysis in development planning. The tool focuses on the gender gap analysis in four aspects: access, participation, control, and benefit of development, between men and women, and the special needs groups. In 2008, Bappenas initiated the GRPB Steering Committee and Technical Teams, which included Ministry of Finance in the board of GRPB’s Steering Committee, together with Bappenas and Ministry of Women Empowerment. The team also included Ministry of Home Affairs; Education; and Health, and formally established by Minister of NationalDevelopment Planning’s decree in 2009. In 2012, Bappenas developed The Gender Equity & Equality Index and Gender Mainstreaming Institutionalization Indicators to measure the progress of Gender Equality in Development. This was followed by the Circular Letter: “National Strategy to Accelerate Gender Mainstreaming through Gender Responsive Planning and Budgeting”, which was signed by four ministers. The National Strategy is developed to ensure that GRPB implementation both at the national and regional level is aligned, systemized, on target and also supporting the practice of good governance, sustainable development, as well as the achievement of the Millennium Development Goals (MDGs). In 2014, GRPB had been implemented in 36 line ministries and 34 provinces